A cidade, entre a cruz e o avião - Paraizo, Mariângela de Andrade (Horizonte, 2006)
This article presents a reading of the relation between the city, death and some of the religions that presided over or consolidated the development of cities. Aiming at investigating the paradigms that oriented the creation and viability of cities in various places and historical periods, it assumes that a reflection on those paradigms, however brief, can provide subsidies for a reading of the contemporary city and the crisis it is facing. In that sense, it focuses on historical and mythical texts, attributing equal value to what is recorded concerning the genesis of cities, in the light of cultural studies. Emphasis is given to the presence of death and the way it propitiated an urge for union in groups. In that context, different religions were the bonds and the reservoir of public space, a necessary condition to preserve ethics. They played the role of re-connecting the living and the dead, natural and supernatural reality, even when they were manipulated in the search for power. This happened, in different ways, until the 19th century, when new institutions and presuppositions emerged. In the 21st century, we witness a crisis in the cities, which, if properly assessed, may lead to the construction of other paradigms, in harmony with contemporary expectations.